MENINGKATKAN KETERAMPILAN MENYIMAK DENGAN MENGIDENTIFIKASI UNSUR INTRINSIK CERITA MENGGUNAKAN KOMBINASI MODEL DISCOVERY LEARNING, THINK PAIR SHARE (TPS) DAN TALKING STICK PADA SISWA KELAS 5 SDN BELITUNG UTARA 1 BANJARMASIN - najwa; Mahmuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low listening skills of students, which negatively affect their learning outcomes in Indonesian language subjects. Contributing factors to this issue include students' lack of concentration during listening activities, weak memory retention, limited language comprehension, and teacher-centered learning approaches. The aim of this study was to improve students' listening skills and learning outcomes through the implementation of a combination of the Discovery Learning, Think Pair Share (TPS), and Talking Stick models. The study employed Classroom Action Research (CAR) using both qualitative and quantitative approaches, conducted over two cycles consisting of four meetings. The research subjects were 18 fifth-grade students at SDN Belitung Utara 1 Banjarmasin. Qualitative data were collected through observations of teacher activities, student engagement, and listening skills. Quantitative data were obtained from both individual and group learning outcomes. The findings revealed that teacher activities were carried out very effectively, student participation increased to a highly active category, listening skills reached a highly proficient level, and learning outcomes achieved a 100% mastery rate. Based on these results, it can be concluded that the combination of Discovery Learning, TPS, and Talking Stick models is effective in enhancing student engagement, listening skills, and academic performance. Therefore, this model is recommended as an alternative teaching strategy for Indonesian language instruction, particularly in identifying intrinsic elements of stories at the elementary school level.